Effects of Lactobacillus plantarum B7 on serum TNF-α and IL-1β level, lipid peroxidation and apoptosis of gastric mucosa in rats infected with Helicobacter pylori - Chompoonut Sunanliganon (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010